Should tularemia be considered a particularly dangerous infection? - L. V. Rubis (Журнал инфектологии, 2024)
Tularemia is a widespread bacterial zoonotic infection in the world, the causative agent of it in our country is classified as pathogenicity group 2, which corresponds to group 3 according to the international classification for laboratory services. F. tularensis is considered a potential agent of category A bioterrorism. The review presents current information about the causative agent of tularemia, the features of the clinical course of the infection and the incidence rate associated with its different subtypes. The possibilities of treatment and prevention of the disease are highlighted. The material is presented from the point of view of whether the infection meets the criteria for a particularly dangerous disease. The species includes 4 subspecies, of which only one, present only in some states of the United States and probably the evolutionarily oldest, is assessed as highly virulent. The subspecies most widespread on the European continent is classified as moderately virulent and causes diseases that do not meet the criteria for a particularly dangerous disease in terms of severe and mortality rate. There is a list of drugs that are quite effective against the causative agent of tularemia, provided they are prescribed in a timely manner. The incidence of tularemia in countries where it is registered does not exceed sporadic levels. However, a feature of the pathogen is plasticity in the external environment which determines the long-term preservation of the epizootic potential of natural foci. In some years large outbreaks of infection occur, often in the absence of visible risk factors. The possibilities of specific and nonspecific prevention are limited and can reduce the risk of infection of the population only with a timely, quick and adequate response to changing situations. In various countries work is underway to create vaccines on different technological platforms, but currently only Russia, Belarus and Kazakhstan use the live attenuated vaccine. Although by wild strains is not a particularly dangerous disease, it requires close surveillance.